Phosphoproteomic changes in response to anoxia are tissue-specific in the anoxia-tolerant crucian carp (Carassius carassius) - Johansen, Anette; Thiede, Bernd; Anonsen, Jan Haug; Nilsson, Göran E. (Frontiers in Physiology, 2024)
Crucian carp (Carassius carassius), a freshwater fish, can survive chronic anoxia for several months at low temperatures. Consequently, anoxia-related physiological and biochemical adaptations in this species have been studied for more than half a century. Still, despite for the well-known role of protein phosphorylation in regulating cellular processes, no studies have comprehensively characterized the phosphoproteome in crucian carp. In this study, we report the global phosphoproteome in crucian carp brain and liver during anoxia and reoxygenation. By applying a bottom-up proteomic approach on enriched phosphopeptides we found that the brain phosphoproteome shows surprisingly few changes during anoxia-reoxygenation exposure with only 109 out of 4316 phosphopeptides being differentially changed compared to normoxic controls. By contrast, in the liver 395 out of 1293 phosphopeptides changed. Although most changes occurred in the liver phosphoproteome, the pattern of changes indicated metabolic depression and decreased translation in both brain and liver. We also found changes in phosphoproteins involved in apoptotic regulation and reactive oxygen species handling in both tissues. In the brain, some of the most changed phosphopeptides belonged to proteins involved in central nervous system development and neuronal activity at the synaptic cleft. Changed phosphoproteins specific for liver tissue were related to glucose metabolism, such as glycolytic flux and glycogenolysis. In conclusion, protein phosphorylation in response to anoxia and reoxygenation showed both common and tissue-specific changes related to the functional differences between brain and liver.